Brazda, brizga, breskvica, fička, finka, fufljica, šiška, roža, špranjica: razmišljanje o prevajanju drame Eve Ensler Vaginalni monologi - Zabukovec, Dušanka (Hieronymus, 2025)
The expressions scatology and coprology originate from Greek: their meaning is studying excrements in connection with food, health and diseases (the meaning of okatos being pus, excrement). They are also connected with sexual fetishism and toilet humour. Man sees this theme as jovial, but it can also express disgust with oneself and misanthropy. Trans-planting the scientific and lexicographical expressions to everyday vocabulary we immediately find ourselves in the field of insults, swearwords and curses. In the past, writers used to pay a lot of attention to obscene vocabulary; they were far from prudery. How did I tackle this problem when – perhaps in a moment of distraction – I agreed to translate Eve Ensler’s play The Vagina Monologues?